Validation of the Brazilian Portuguese version of the Rapid Eye Movement Sleep Behavior Disorder Screening Questionnaire (RBDSQ-BR) - PENA-PEREIRA, Márcio Alexandre; SOBREIRA-NETO, Manoel Alves; SOBREIRA, Emmanuelle; CHAGAS, Marcos Hortes Nisihara; OLIVEIRA, Daniel Sabino de; RODRIGUES, Guilherme Riccioppo; SOUZA, Carolina Pinto de; ECKELI, Alan Luiz; FERNANDES, Regina Maria França; TUMAS, Vitor (Arquivos de neuro-psiquiatria, 2020)
ABSTRACT Introduction: A diagnosis of rapid eye movement sleep behavior disorder (RBD) currently requires confirmation with polysomnography (PSG). However, PSG may not be sufficiently available. In these situations, a clinical diagnostic measure might be useful. Objective: To validate the Brazilian Portuguese version of RBD screening questionnaire (RBDSQ) for patients with Parkinson’s disease (PD). Methods: Using detailed clinical interviews and PSG analysis (diagnostic gold standard), a convenience sample of 69 subjects was divided into the following subgroups: patients with PD and RBD (PD+RBD; n=50) and patients with PD alone (PD-RBD; n=19). Results: RBDSQ-BR showed adequate internal consistency (Cronbach’s α=0.809) and, except for item 8, adequate item-test correlation. The retest performed in a second sample (n=13, consecutive) showed high agreement for total score (intraclass correlation coefficient, ICC=0.863) and acceptable agreement for items 2, 3, 6.2, 6.3, 7, and 8 (K>0.60). The receiver operating characteristic (ROC) curve analysis had an area under the curve (AUC) of 0.728. A cut-off score of 4 enabled the correct diagnosis of 76.8% subjects and provided the best balance between sensitivity (84%) and specificity (57.9%), with a 2.0 likelihood ratio of a positive result (LR+) and a 0.3 likelihood ratio of a negative result (LR-). Items 2 and 6.2 had 84.2% specificity and 3.2 LR+. Combined items 1+2+6.2, 2+6.1, and 6.1+6.2 increased the specificity to 94.7%, with LR+ ranging from 6.1 to 7.6. Conclusions: RBDSQ-BR is a reliable instrument, which may be useful for RBD diagnosis of Brazilian patients with PD. The instrument is also valid and may help in a better selection of cases for a more detailed clinical evaluation or even PSG analysis.